Synthesis, Herbicidal Evaluation, and Structure-Activity Relationship of Benzophenone Oxime Ether Derivatives - Jimei Ma; Mingwei Ma; Linhao Sun; Zhen Zeng; Hong Jiang (Journal of Chemistry)
A novel series of benzophenone oxime ether derivatives with tertiary amine groups were synthesized and their herbicidal activities of 24 compounds against Oryza sativa, Sorghum sudanense, Brassica chinensis, and Amaranthus mangostanus L. were also evaluated. Most of these compounds exhibited significant inhibitory effect on root growth at 20 ppm. Based on the herbicidal activity data, computational Three-Dimensional Quantitative Structure-Activity Relationship (3D-QSAR) analysis and molecular docking were undertaken. CoMFA contour maps were generated for the design of benzophenone oxime ether analogues with enhancing activity.